Segmentação e roteamento de VLAN's em servidores Linux utilizando o protocolo 802.1Q - Wagner, Daniel Ernesto (2012)
Because of the need to increase security, privacy and improve network performance by optimizing resources come with the proposal to use the segmentation by creating vlan's, increasing security and privacy of information contained in each subnet created, improving the use of a DMZ for use of equipment and services common to several subnets and even access external dependencies department, using the customization of linux operating system kernel, supporting IEEE 802.1Q protocol thus recognizing a single interface the ethernet `TAG 's VID so one device can do the whole job redirection, interconnection, service and DHCP server still filtering rules through free software, not hardware or using proprietary software. For related procedures that indicate that material forms and resources needed to achieve this goal.